Diffusion chronometry and the timescales of magmatic processes - Costa, Fidel (2020)
Volcanic eruptions can represent major societal hazards. Placing tighter bounds on the timescales of magmatic processes that precede eruptions is, therefore, important for volcano monitoring and forecasting. Diffusion chronometry, where volcanic crystals that contain chemical gradients are treated as time capsules, allows the timescale of various magmatic processes to be constrained. In this Review, we discuss the basics of diffusion chronometry and describe how re-equilibration via chemical diffusion provides insights into the timescales of magma storage, ascent and eruption. Crystals from mafic volcanoes record timescales of days to years between magma intrusion and eruption, which broadly match those recorded by monitoring data (such as increased seismicity). The timescales recorded in crystals from large silicic calderas, however, are typically longer than those from mafic volcanoes, spanning decades to millennia, but almost two orders of magnitude shorter than the timescales obtained by U-Th isotope disequilibria in zircon. The cause of this discrepancy is debated but likely reflects the protracted magma accumulation and complex thermal history that many crystals experience before eruption. Diffusion chronometry adds the fourth dimension to volcano science (that is, time), and advances in analytical and experimental approaches (such as NanoSIMS) open up new opportunities for understanding magmatic systems.